2015
DOI: 10.1002/smr.1703
|View full text |Cite
|
Sign up to set email alerts
|

Crafting a software process improvement approach-a retrospective systematization

Abstract: Structured approaches are beneficial for successful software process improvement (SPI). However, process engineers often struggle with standardized SPI methods, such as capability maturity model integration (CMMI) or International Organization for Standardization (ISO) 15504, and complain about too generic or voluminous approaches or methods that are alien to the organizations in which SPI is conducted. Therefore, process engineers need to customize existing SPI models or develop new approaches for companyspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Requirements regarding the validity of the results differ as well as the general scope of experiments. Furthermore, as we have previously discussed, small and very small companies usually have insufficient resources to invest in the necessary preparation and allocation of resources (Kuhrmann, 2015). Nevertheless, experimentation allows for, e.g., evaluating different methods and tools, building a hypothesis, and testing the hypothesis.…”
Section: Computer Sciencementioning
confidence: 99%
“…Requirements regarding the validity of the results differ as well as the general scope of experiments. Furthermore, as we have previously discussed, small and very small companies usually have insufficient resources to invest in the necessary preparation and allocation of resources (Kuhrmann, 2015). Nevertheless, experimentation allows for, e.g., evaluating different methods and tools, building a hypothesis, and testing the hypothesis.…”
Section: Computer Sciencementioning
confidence: 99%
“…In this course of thinking, Gray et al [23] proposed an incremental approach to process assessment and improvement based on variety of assessment techniques. Guidelines for designing software process assessment and improvement approaches are presented in [63,33]. Zarour et al [62] presented a systematic literature review on designing and implementing lightweight assessment methods based on top-down best practice, and concluded that success of assessment contributes to success of SPI as a whole.…”
Section: Software Process Assessmentmentioning
confidence: 99%
“…As described in [14], ArSPI defines five key artefacts (Table 1), which have to be created in every SPI project. 24 support artefacts, created in response to particular project requirements, for example, assessment and quality assurance artefacts, accompany these key artefacts.…”
Section: Arspi Artefact Modelmentioning
confidence: 99%